(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the hygienic-sanitary quality of frozen fruit pulps sold in the city of Limoeiro do Norte- CE. Two batches of acerola, cashew and guava frozen fruit pulps from eight commercial brands (A, B, C, D, E, F, G and H), totaling 48 samples, purchased at the local store of Limoeiro do Norte, from July 2019 to February 2020, were analyzed. The analyzes carried out were: microbiological (total and thermotolerant coliforms, Escherichia coli, Salmonella sp. and molds and yeasts) and microscopic (light and heavy foreign matter). The results indicated that the samples from Batch 1 and 2 were not in accordance with the Normative Instruction 60 of December 23, 2019 of ANVISA. As for Normative Instruction 01 of January 7, 2000 from MAPA, for fruit pulps in Batch 1 and Batch 2, 41.6% and 37.5% of the samples, respectively, were in disagreement. All samples showed no salmonela, but for thermotolerant coliforms there was growth of up to 1,5 × 102 CFU g-1. The brand D was the only one that did not show any microbial growth in the acerola, cashew and guava pulps. As for macroscopic analyzes, the fragments found were metal, colored plastics and textile thread. The brands E and H showed no dirt. The brands B and D, on the other hand, had the higher amount of foreign matter. This study showed that the analyzed industries need to implement a standardized quality program, as there was variation in the microbiological and microscopic results.